Sjögren’s Syndrome–Vasculitis: Azathioprine Induced Myelosuppression–A Case Report - Reddy, Kunduru Buchi; priya, Banothu Vishnu; Navya, Beemarthi; Mahender, Vatipelli (Indian Journal of Pharmacy Practice)
Sjögren's syndrome is a chronic autoimmune disease causing destruction of exocrine glands, due to lymphocytic infiltration predominately affects middle age women. Sjogren's syndrome classified may be either primary or secondary Sjogren's syndrome. The prevalence of primary Sjögren's syndrome is approximately 0.5–1.0%, while 30% of patients with autoimmune rheumatic diseases suffer from secondary Sjögren's syndrome. Treatment focuses on relief of the symptoms affecting particular areas of the body. Glucocorticoids (Prednisolone) and/ or immunosuppressive agents (azathioprine) are indicated for the treatment of systemic vasculitis. In this case, the patient is suffering from Sjogren’s syndrome and patient was prescribed with a glucocorticoid and an immunosuppressive agent (azathioprine). Use of Azathioprine has lead to myelosuppression. So, the dosing schedule of these drugs are important and dosing of drug should be done according to the patient response and at the same time check for adverse effects during course of treatment and any altered lab parameters.
Keywords: Sjögren's syndrome; Vasculitis; Azathioprine; Prevalence; Myelosuppression